Prototipe Model Pembelajaran REC (Reading, Exercise, and Clarification) untuk Pembelajaran IPA SMP - Rachmawati Rachmawati; Indrawati Indrawati; Sutarto Sutarto (Program Studi Magister Pendidikan IPA FKIP Universitas Jember Bekerjasama dengan Perkumpulan Pendidik IPA Indonesia (PPII), 2016)
Efforts to increase the active learning that is centered on students in science learning process can be done through learning that emphasize reading skills, training, and clarification. The purpose of this study was to produce a prototype model of learning that can facilitate the role of teachers and students to achieve the purpose of active learning. REC prototype model of learning (reading, exercise, and clarification) for junior high school science teaching is designed to produce a model based learning students. This study design is a 4-D which consists of four main stages, namely; 1) Define (definition), 2) Design (Design), 3) Develop (Development) and 4) Disseminate (Deployment). The result of this research is a learning model prototype REC (reading, exercise, and clarification) for junior high school science teaching consists of sintakmatik, social system, the principle of reaction, support systems, instructional impact and impact accompanist.